Antecedents and Outcomes of Brand Identification with Apple Products among Iranian Consumers. Issue 2 (3rd April 2021) - Fazli-Salehi, Reza; Azadi, Mohammad; Torres, Ivonne M.; Zúñiga, Miguel Ángel
Abstract: This study evaluates the antecedents and outcomes of brand identification with Apple products on purchase intention among Iranian consumers. Our objectives were to assess self-expressiveness (as a hedonic aspect) and perceived quality (as a utilitarian aspect) to examine the drivers of consumers' brand identification. This study evaluates the effect of brand identification on brand loyalty as well as the effect of brand social self-expressiveness (as a social factor) and perceived quality (as a utilitarian aspect) on brand identification. The studied population consists of all customers of digital goods who have owned at least one Apple product in the past. In this study, 9 stores located in Tehran were selected and 600 questionnaires were delivered data collection. The data collected was analyzed using structural equation modeling (SEM). The results of this study reveal that brand identification positively affects both purchase intention and brand loyalty. Additionally, the findings reject the role of perceived quality as an effective factor in brand identification. However, self-expressiveness was found to affect purchase intention and loyalty, through a mediation effect of brand identification. This study contributes to social identity and self-expansion theory as well as benefits marketers understand the dynamics of consumers' brand identification.